Sports coaching the basics - Purdy, Laura G. (The Basics, 2018)
"Sports Coaching: The Basics is an engaging and provocative introduction to sports coaching which combines coaches' views and experiences of their work with discussions and topical issues that feature in this fast-growing field. In doing so, it places the coach at the centre of the discussion as it explores a range of ideas relating to philosophical, historical, sociological, psychological and pedagogical interpretations of contemporary practice. Consequently, the book prompts questions such as: - What is coaching? - What does it mean to be a coach? - How do coaches influence athletes/players? - How do coaches learn? - What is it like to be a coach? Readers are encouraged to reflect upon their experiences of coaching and to start conversations about coaches' work. Therefore, the book is of use for coaches, those interested in studying sports coaching, and coach educators or facilitators of coach learning initiatives." --Provided by publisher.